Postoperative Imaging Findings following Sigmoid Sinus Wall Reconstruction for Pulse Synchronous Tinnitus - Raghavan, P.; Serulle, Y.; Gandhi, D.; Morales, R.; Quinn, K.; Angster, K.; Hertzano, R.; Eisenman, D. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: Transmastoid sigmoid sinus wall reconstruction is a surgical technique increasingly used for the treatment of pulsatile tinnitus arising from sigmoid sinus wall anomalies. The imaging appearance of the temporal bone following this procedure has not been well-characterized. The purpose of this study was to evaluate the postoperative imaging appearance in a group of patients who underwent this procedure.MATERIALS AND METHODS: The medical records of 40 consecutive patients who underwent transmastoid sigmoid sinus wall reconstruction were reviewed. Thirteen of 40 patients underwent postoperative imaging. Nineteen CT and 7 MR imaging examinations were assessed for the characteristics of the materials used for reconstruction, the impact of these on the adjacent sigmoid sinus, and complications.RESULTS: Tinnitus resolved in 38 of 40 patients. Nine patients were imaged postoperatively for suspected complications, including dural sinus thrombosis, facial swelling, and wound drainage. Two patients underwent imaging for persistent tinnitus, and 2, for development of tinnitus on the side contralateral to the side of surgery. The materials used for reconstruction (NeuroAlloderm, HydroSet, bone pate) demonstrated characteristic imaging appearances and could be consistently identified. In 5 of 13 patients, there was extrinsic compression of the sigmoid sinus by graft material. Dural sinus thrombosis occurred in 2 patients.CONCLUSIONS: The imaging findings following sigmoid sinus wall repair are characteristic. Graft materials may result in extrinsic compression of the sigmoid sinus, and this finding may be confused with dural venous thrombosis. Awareness of the imaging characteristics of the graft materials used enables this differentiation.PSTpulse synchronous tinnitusSSWRsigmoid sinus wall reconstruction